ENDOWED AND CREATED RESOURCES TOWARDS ECOTOURISM COMPETITIVENESS: NATURAL PROTECTED AREAS IN SARAWAK - Jun Zhou, Thong; Abang Azlan, Mohamad; May Chiun, Lo (Editura Universitati din Oradea, 2020)
The richness of natural areas in Malaysia leads ecotourism to become one of the rapidly growing industries within the nation. The present study aims to discover the impacts of endowed and created resources on ecotourism competitiveness from both domestic and international tourists’ perspectives. 189 respondents had completed the questionnaire and WarpPLS 6.0 was used to test the model created. The results revealed that endowed resources (e.g. natural resources and cultural heritage attraction) are positively and significantly correlated to ecotourism competitiveness. Surprisingly, created resources (e.g. tourism infrastructure and range of activities) were observed to have no significant relationship with ecotourism competitiveness.